Analysis of Philosophy in History and Its Implications for Christian Religious Education in the Digital Era - Wowor, Vroly R.; Krikhoff, Rudy Arianto (STT Pelita Dunia, 2025)
Philosophy plays a crucial role in shaping theological thought and contributing to Christian religious education. Throughout history, philosophy has served as an instrument for understanding existence, morality, and truth, influencing the development of theological education methods. However, the digital era presents new challenges in conveying Christian teachings. The ease of access to information has led to the widespread dissemination of theological interpretations that do not always align with sound doctrine, necessitating a systematic philosophical approach to uphold the integrity of Christian education. This study employs a qualitative method with a literature review approach, focusing on historical and conceptual analysis. The data sources consist of books, scholarly journals, and academic documents that discuss the historical development of philosophy and its implications for Christian religious education in the digital era. The analytical technique applied is philosophical hermeneutics to interpret philosophical concepts in relation to the transformation of theological education. The findings reveal that philosophical thought from various eras has significantly influenced theological teaching methods, particularly within rationalist, scholastic, and postmodernist frameworks. The primary challenge for Christian education lies in utilizing technology wisely without compromising spiritual essence. The integration of critical philosophy and apologetics emerges as a key strategy in fostering a strong understanding of faith amid the rapid spread of digital information. Christian religious education must adapt to technological advancements while steadfastly upholding fundamental faith values.